Facilitating placements of graduate students to build capacity for National Agriculture Research and Extension System: The case of iAGRI in Tanzania - Chindime, M. S.; Uwituze, S.; Nampala, M. P.; Osiru, M.; Adipala, E. (RUFORUM Working Document Series, 2016)
The attainment of sustainable food security in Africa, as elsewhere, requires the efforts of a cadre of innovative well-trained agriculture specialists who are familiar with the constraints and perspectives of national priority needs. In light of this, a USAID-sponsored partnership among six American Land Grant universities, Tanzanian Government, the Regional Universities Forum for Capacity Building in Agriculture (RUFORUM) and the Global South universities was established in 2011 to implement Innovative Agricultural Research Initiative (iAGRI). The focus was to help strengthen human and institutional capacity for agricultural research for development in Tanzania. As part of the implementation of the programme, RUFORUM was sub-contracted by the Ohio State University to coordinate the training of Tanzanians in selected universities in Africa for Master of Science and PhD Degrees in disciplines identified as priority areas for Tanzania. The iAGRI project training model involved course work at the host university and research in Tanzania under the supervision of the academic supervisors from the host university and a local supervisor from Tanzania, majority being from Sokoine University of Agriculture (SUA). The model also included a compulsory student participation in scientific conferences, skills enhancement short trainings, and travel to Tanzania by university supervisors to check on students and interact with the Tanzanian supervisors. A total of 31 students (30 MSc and 1 PhD) under RUFORUM coordination were successfully placed in nine Universities in Eastern and Southern Africa to undertake postgraduate training in 16 selected programmes of strategic interest to the Tanzania National Agricultural Research and Extension System (NARES). Of the 31 students placed, 65% have completed their degree programmes and reported back to their respective institutions in Tanzania and the rest are due to graduate by end of February 2017. The placements provided a platform for exposure and cross learning among the participating institutions and graduates have gained relevant skills to effectively contribute to the development of the agriculture sector in Tanzania. They have also been linked to close to 2,000 students and graduates across Africa. The implementation process has demonstrated the need for flexible approaches that not only take into account the needs of the sending institutions but also those of the host institutions. The additional skill enhancement trainings, field/industry attachment, regional and international exposure, and link to the wider community of graduate students and research community enhance the quality and relevance of training and wider interconnection across Africa. The iAGRI model presents learning opportunities for similar projects that are linked with academic mobility.
Keywords: Academic mobility; Higher agricultural education; iAGRI; RUFORUM; Tanzania